"Seni Teks" Dalam Prespektif Dunia Virtual - Rahmat Jabbaril (Jurnal Budaya Nusantara, 2021)
If that is the priority in weighing the mind and exploring the core of the perspective of thinking, of course, will move on to a "statement". Where the platform of thought will be the entrance and open a gap for other thoughts, because the thinking perspective finds the value of "abstract". The context of thinking is more about extracting the essence of thinking, so the value of art becomes abstract. The reality of the meaning of art is not only a question of form, but more than that, art will play freely about form. The basic theory of writing, using a qualitative frame of mind, using a curatorial approach. The form of virtue in art is actually not based on purely aesthetic values, but the depth of ideas as a way of "enlightenment" to determine the direction where we should be oriented. The result of this thought is, the continuity of artistic value is certainly constructed by; Awareness of the value of intensity, ethics-technique, psychology and full awareness of the essence of ideas (philosophy of art). So the perspective of virtue in art is the awareness of thinking about the abstraction of the universe itself, which is manifested in the form of works, namely the work of two dimensions of Text Art.